Sistem Informasi Gereja Berbasis Website di Kecamatan Salo dan Bangkinang Kota Kabupaten Kampar - Alfredo Siagian; Safni Marwa; Kasini (Jurnal Inovasi Teknik Informatika, 2025)
The web-based church information system in Salo and Bangkinang Kota Districts, Kampar Regency, is designed to improve efficiency and accuracy in disseminating information and managing church data. Churches in this region still use manual methods to share worship schedules and activities, which creates challenges for congregants and visitors in accessing essential information. This study aims to analyze, design, and develop a web-based church information system that can be accessed anytime and anywhere. The research employs the Prototype method, with system testing conducted using Black Box Testing. The system is developed using the PHP programming language, the CodeIgniter framework, and MySQL database. The findings indicate that the system successfully provides real-time worship information and simplifies church data management, including congregation numbers, vision and mission, and church history. The system fulfills functional requirements with a 100% success rate. This system enhances communication, data management, and church services, making worship schedules and church activities more easily accessible to congregants, the local community, and newcomers. Keywords: Church Information System, Website, UI, Efficiency, Prototype.